The Routledge companion to mindfulness at work - Dhiman, Satinder (Routledge, 2020)
"Given the ever-growing interest in the benefits of mindfulness to organizations and the individuals who work in them, this Companion is a comprehensive primary reference work for mindfulness (including creativity and flow) in the workplace, including business, healthcare and educational settings. Research shows that mindfulness boosts creativity through greater insight, receptivity and balance, and increases energy and a sense of wellbeing. This Companion traces the genesis and growth of this burgeoning field, tracks its application to the workplace, and suggests trends and future directions. With contributions from leading scholars and practitioners in business, leadership, psychology, healthcare, education, and other related fields, The Routledge Companion to Mindfulness at Work is an extensive reference work which will be a vital resource the fields of management and organizational studies, human resource management, psychology, spirituality, cultural anthropology and sociology. Each chapter will present a listing of key topics, a case or situation that illustrates the application of the themes, workplace lessons and reflection questions"--